Multivariate analysis of mineral content associated with flesh browning disorder in ‘Fuji’ apples produced in Southern Brazil - Correa T.R. (2017)
© 2017, Instituto Agronomico. All rights reserved.Flesh browning is a physiological disorder that occurs in ‘Fuji’ apples during storage, which causes considerable postharvest losses of fruit produced in Southern Brazil. This work aimed to assess the mineral attributes [Ca; Mg and K contents and the Mg/Ca; K/Ca and (K + Mg)/Ca ratios] associated with the flesh browning disorder incidence, as well as to identify which of these mineral attributes better discriminate the differences in the degree of susceptibility to flesh browning disorder in ‘Fuji’ apples stored under controlled atmosphere (CA; 1.2 kPa O2 + 2.0 kPa CO2 and 1.2 kPa O2 + < 0.5 kPa CO2; 0.5 ± 0.1 °C and 96 ± 2% RH, during an 8-month period). Apples from 2 orchards in Fraiburgo, Santa Catarina, 3 orchards in São Joaquim, Santa Catarina, and 3 orchards in Vacaria, Rio Grande do Sul were used. The fruit with flesh browning disorder has lower levels of Ca and a higher Mg/Ca ratio when compared to the fruit without flesh browning. The Mg and K contents were not related to the physiological disorder. The canonical discriminant analysis (CDA) showed that the isolated Ca content better discriminated the fruit with and without flesh browning disorder. ‘Fuji’ apples with Ca contents < 80 mg∙kg−1 in the flesh present a greater risk of developing this disorder in the Southern Brazil production region.